Página web para agendamiento, control y modificación de citas para la empresa Kasa Dinava (2024)
The company Kasa Dinava, an authorized distributor of kitchen utensils and healthy cooking workshops, is facing a significant challenge in the internal management of workshop appointment scheduling. Currently, conventional and physical methods are being used to carry out this activity, leading to a lack of organization, distortion of information, and ineffective communication with customers.